Initial Experience Of Laparoscopic Incisional Hernia Repair - Biswas, SK; Arefin, MM; Saha, JC; Ahmed, T; Rahman, MM (Faridpur Medical College Journal, 2011)
The laparoscopic incisional hernia repair is a safe alternative to open mesh repair. The procedure has the advantages of minimal access surgery and lower recurrence rate. A prospective study of laparoscopic incisional hernia repair of our first 11 patients was performed from July 2008 to December 2009. No serious intraoperative or postoperative morbidity was encountered, only two patients developed seroma. The mean operating time was 90 minutes (60 to 180 minutes). The mean day of discharge after surgery was 3 days (2-7 days). No patient developed a recurrence during mean follow up period of 10 months. Laparoscopic repair of incisional hernia has been shown to be feasible, safe and effective. However, careful patient selection and acquiring the necessary advanced laparoscopic surgical skills coupled with the proper use of equipment are mandatory before embarking on this procedure. Key Words: Incisional hernia; Laparoscopic repair; Mesh; Polypropylene DOI: 10.3329/fmcj.v5i2.6819 Faridpur Med. Coll. J. 2010;5(2):41-45